The Relationship between Nocturnal Enuresis and Obstructive Sleep Apnea in Children - María Andreu-Codina; Danica Nikolic-Jovanovic; Eduard Esteller; Núria Clusellas; Montserrat Artés; Javier Moyano; Andreu Puigdollers (Children)
Background: The aim of this study is to determine the prevalence of nocturnal enuresis (NE) in children with obstructive sleep apnea (OSA), the effect of adenotonsillectomy (AT) and the width of the arches, and to compare them with control children without respiratory problems. Methods: Children from 2 to 12 years old were divided into three groups: children with OSA and NE (n = 51), children with OSA without NE (n = 79), and the control group (n = 168). NE was defined as at least one bedwetting incident per month. Arch widths were measured at the baseline and one year after. OSA was diagnosed by means of polysomnography, and the apnea-hypopnea index (AHI) was obtained. Parents completed the Pediatric Sleep Questionnaire (PSQ) to classify their children into those with and without NE. Results: NE was present in 39.2% of children with OSA compared to 28% in the control group (p = 0.04). After AT, 49% of the children with OSA and NE significantly improved. Both OSA groups had narrower arch widths than the control group (p = 0.012), with the NE group having the narrowest widths. NE is more prevalent in children with OSA and should be considered one of the first signs of breathing disorders. Adenotonsillectomy reduces NE in about half of the affected children. Both arch widths are narrower in children with OSA, particularly in those with NE.